Once BITTEN, Twice Shy: An Applied Trauma-Informed Healthcare Model. (October 2019) - Lewis, Chrystal L.; Langhinrichsen-Rohling, Jennifer; Selwyn, Candice N.; Lathan, Emma C.
Nurses need a pragmatic theory to understand and respond to the impact of vulnerable patients' previous healthcare experiences, as these are likely to influence response and adherence to treatment plans. The authors of this paper present the new BITTEN (B etrayal history by health-related institutions, I ndicator for healthcare engagement, T raumas related to healthcare, T rust in healthcare providers, patientE xpectations andN eeds) Model of Trauma-Informed Healthcare. BITTEN identifies patients' current healthcare expectations and needs as a function of their previous betrayal by healthcare systems, which operates in conjunction with their current health indicators to potentially trigger trauma symptoms and impact trust in healthcare providers.